2018
DOI: 10.1002/cjoc.201800450
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Chemistry of N‐Heterocyclic‐Carbene‐Functionalized Metal‐Nanoparticles and Their Applications

Abstract: Metal-nanoparticles (M-NPs) have been widely applied in catalysis, imaging, sensing and medicine. One particularly active area of this research is the modification of the surface of the nanoparticles to prevent aggregation through the coordination of ligands. N-Heterocyclic carbenes (NHCs) have emerged as suitable ligands for this purpose due to their affinity to the metals and their strongly electron donating nature. A number of rationally designed NHC-modified M-NPs have been developed using strategies based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 127 publications
0
26
0
Order By: Relevance
“…On the other hand, although M‐NPs synthesized within cage templates have proven to be more stable and efficient catalysts than their conventional counterparts in a few catalytic reactions, a large number of catalytic reactions remain to beexplored, as well as a range of other potential applications. Furthermore, given recent high‐profile progress made in N ‐heterocyclic carbene (NHC)‐modified M‐NPs, we look forward to the future use of a range of porous NHC‐precursor cages as templates in the controlled synthesis of M‐NPs.…”
Section: Potential and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although M‐NPs synthesized within cage templates have proven to be more stable and efficient catalysts than their conventional counterparts in a few catalytic reactions, a large number of catalytic reactions remain to beexplored, as well as a range of other potential applications. Furthermore, given recent high‐profile progress made in N ‐heterocyclic carbene (NHC)‐modified M‐NPs, we look forward to the future use of a range of porous NHC‐precursor cages as templates in the controlled synthesis of M‐NPs.…”
Section: Potential and Challengesmentioning
confidence: 99%
“…Metal nanoparticles (M‐NPs) have attracted tremendous interest in recent years due to their unique physical and chemical properties resulting from their size reduction and shape variation . In particular, the use of ultra‐small M‐NPs as efficient catalysts in various reactions is a rapidly growing area of research as a consequence of their synthetic accessibility and superior catalytic efficiency . However, due to their high surface energy, small M‐NPs are prone to aggregation during reactions and associated loss of their catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that NHC ligands have the ability to enhance nanocrystal catalyst stability and increase nanocrystal catalyst activity and/or selectivity. [9][10][11][12] NHC-stabilized nanocrystals have been shown to display catalytic activity toward, for example, hydrogenations and semihydrogenations, 9,[12][13][14] lactonization, 10 asymmetric arylations, 15 Buchwald-Hartwig aminations, 16 and cross-coupling reactions. 15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] NHC-stabilized nanocrystals have been shown to display catalytic activity toward, for example, hydrogenations and semihydrogenations, 9,[12][13][14] lactonization, 10 asymmetric arylations, 15 Buchwald-Hartwig aminations, 16 and cross-coupling reactions. 15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction. 11,17 For example, Cao et al investigated the use of NHC-stabilized Au nanocrystals as electrocatalysts for the reduction of CO2 to CO. Interestingly, the Au nanocrystal catalyst with surface-bound carbene ligands exhibited a higher Faradaic efficiency for CO2 reduction to CO than did bare (or ligand-less) Au nanoparticles; it was further shown that the NHC affected the mechanistic pathway of catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation